Synthesis of La2NiMnO6 Double Perovskite as a Highly Selective Electrocatalyst for Oxygen Reduction to Hydrogen Peroxide in Electrochemical Energy Conversion - Hossain, Mohammad Imran; Monim, Syed Abdul; Moushumy, Zannatul Mumtarin; Khansur, Neamul Hayet; Mahmud, Iqbal; Rahaman, Mostafizur; Aldalbahi, Ali; Firoz, Shakhawat H.; Hasnat, Mohammad A. (ACS Applied Energy Materials, 2025)
Oxygen reduction reaction (ORR), a key process in sustainable energy conversion, utilizing a perovskite catalyst to achieve higher currents at lower overpotentials along with the production of value-added product hydrogen peroxide (H2O2), serves the dual functionality of both energy production and a green route for H2O2 generation. Here, we report the synthesis of a highly efficient double perovskite La2NiMnO6 (LNMO), achieved through the incorporation of two transition metals, Ni and Mn, in the perovskite structure, and explore its activity for ORR. During ORR at a rotation rate of 1600 rpm in 1.0 M NaOH, LNMO exhibits an onset potential of 0.75 V (corresponding to a current density of 0.1 mA cm-2) and a Tafel slope of 95 mV dec-1, achieving over 88% H2O2 selectivity and 73% faradaic efficiency across a wide potential range of 0.2-0.6 V vs RHE. Characterization techniques including OCP, EIS, ICP-OES, XRD, XPS, FE-SEM, and FTIR confirmed the successful preparation of LNMO and its catalytic activity. The kinetic investigation unveiled by the transfer coefficient (α) demonstrated that ORR on the LNMO surface followed a stepwise mechanism, involving an overall two irreversible electron transfer steps, where the first electron transfer was the rate-determining step. The analyses further revealed a diffusion-limited process for ORR accompanied by first-order kinetics with a standard rate constant (k0) of 3.97 × 10-3 cm s-1 and a formal potential (E0) value of 0.96 V vs RHE. Finally, a stability test via chronoamperometry showed that LNMO outperformed the Pt/C catalyst.
CRIS-Team Scopus Importer:2025-02-07
Keywords: double perovskite; energy conversion; kinetics; La; mechanism; oxygen reduction reaction (ORR)